Investigation of Insulin Receptor Substrate-1 and the Prevalence of Type 2 Diabetes Mellitus among Hepatitis C Infected Patients - Aklo, Mohammed Ghali; AL-Mudhafar, Dhefaf Hameed (Medical Science Journal for Advance Research, 2024)
Background: The hepatitis C virus causes a lot of deaths and illnesses across the world. It accounts more than 20% of hepatocellular carcinoma and chronic liver disease patients. In addition to causing liver illness, hepatitis C virus infection may produce extrahepatic symptoms, such as autoimmune diseases. Type 2 diabetes is more common in these individuals. There is strong evidence to support this theory, since research has shown that hepatitis C virus (HCV) infected individuals are more likely to develop type 2 diabetic mellitus (DM). Aim of the study: Estimation level of insulin receptor substrate-1 and prevalence DM in HCV patient. Material and Methods: It is a case-control study that was held in Najaf governorate between July 2023 and December 2023 with a sample size of 128 subjects. The subject group included 128 (41 males and 23 females) HCV-infected patients, and the control group attended the specialized center for gastroenterology and hepatology and the public health laboratory. Their ages ranged from 26 to 70 years. Used ELISA Tanique for estimation of IRS-1, HCV IgG, and HbA1c and estimation of AST, ALT, and ALP in a spectrophotometer. The SPSS software package for Windows, version 27 (Build 27.0.1.0, copyright © IBM Corp., 2022, USA), was used to analyse the data. Conclusion: The hepatitis C virus leads to the destruction of IRS-1 in different ways and causes insulin resistance and type 2 diabetes mellitus.